THE COASTLINE DF FORTALEZA CITY. A PRODUCT OF ENVIRONMENTAL IMPACTS CAUSED BY THE MUCURIPE HARBOR - Maia, Luis P.; Jimenez, José A.; Serra, Jordi; de Morais, Jáder O. (Arquivos de Ciências do Mar, 2018)
The coastal conflicts originated lly the successive implementations of a harbor along the Fortaleza coast (NE Brazil) during the last century are illustrated in this paper. Because ali the designed layouts and the different locations selected for the harbor were dane without considering the local coastal dynamics, the use itself entailed port shoaling and the system was rapidly degraded with coastal erosion. Since the economical benefits generated with the port was a priority for planners, solutions were mainly designed to optimize port exploitation without paying attention to the coastal response. The interest in mitigating the resource degradation appeared with the occurrence of extensive coastal damages and the nearly full disappearance of the beach in some stretches. Moreover, the appearance of a new coastal use, i.e. tourism, with a potential economic importance higher than the previous one, i.e .trading, has originated a growing awareness in coastal zone management in the Fortaleza's "coastal" way of thinking.